2015
DOI: 10.4103/0972-124x.156881
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and occurrence of gingival recession - An epidemiological study

Abstract: Objectives:Gingival recession is the term used to characterize the apical shift of the marginal gingiva from its normal position on the crown of the tooth. It is frequently observed in adult subjects. The occurrence and severity of the gingival recession present considerable differences between populations. To prevent gingival recession from occurring, it is essential to detect the underlying etiology. The aim of the present study was to determine the occurrence of gingival recession and to identify the most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
1
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 25 publications
9
50
1
17
Order By: Relevance
“…Gingival recession is one of the most common esthetic and functional concerns associated with periodontal tissues. 13 A variety of precipitating factors have shown to be associated with recession of gingival margin: oral hygiene habits like traumatic tooth-brushing & tooth malpositioning, 14 high frenum or muscle attachment, 15 alveolar bone dehiscence, 16 plaque & calculus 17 and iatrogenic factors related to restorative and periodontal treatment procedures. 18 Clinically gingival recession results in exposed root surfaces and loss of marginal tissue attachment.…”
Section: Resultsmentioning
confidence: 99%
“…Gingival recession is one of the most common esthetic and functional concerns associated with periodontal tissues. 13 A variety of precipitating factors have shown to be associated with recession of gingival margin: oral hygiene habits like traumatic tooth-brushing & tooth malpositioning, 14 high frenum or muscle attachment, 15 alveolar bone dehiscence, 16 plaque & calculus 17 and iatrogenic factors related to restorative and periodontal treatment procedures. 18 Clinically gingival recession results in exposed root surfaces and loss of marginal tissue attachment.…”
Section: Resultsmentioning
confidence: 99%
“…In past many of the different studies has been done to investigate associated factors of Gingival Recession. 1,11 , In our study we will chose younger population of Jamshoro city to investigate most common causes of gingival recession so that we can be to do early treatments for this problematic condition.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Many studies have been done in different parts of the world on the prevalence of gingival recession their results revealed that approximately more than 50% of the population has high prevalence of gingival recession among younger population. 11,[15][16][17] Surveys also exposed that the presence and level of gingival recession will be increased with increasing age. 11,18 In our study assess main etiological factors associated with gingival recession mostly in young individuals, our results from different clinical examinations and history we found that the presence of gingival recession in younger population of Jamshoro city may interconnected to traumatic or faulty(aggressive tooth brushing) mal-positioned teeth were also showed recession, and tobacco consumer also indicated this condition, it has given us clue that recession can might be a multi-factorial disease, in which one type is being related with anatomical factors and on the other hand another type is with physiological or may be pathological factors,…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome was the percentage of root coverage. Secondary outcomes were as follows: (a) probing depth: distance from the gingival margin to the bottom of the gingival sulcus; (b) recession width: measured at the greatest width of the defect; (c) recession depth: distance from the CEJ to the gingival margin; (d) width of keratinized tissue: distance from the gingival margin to the mucogingival junction; (e) gingival thickness: measured 2‐3 mm apical to the free gingival margin (at the mid‐buccal aspect) by penetrating a #15 endodontic file with a rubber stop into the tissue; and (f) clinical attachment level: distance from the CEJ to the bottom of the sulcus …”
Section: Methodsmentioning
confidence: 99%